The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.ejphar.2015.03.057
|View full text |Cite
|
Sign up to set email alerts
|

Increased Rho-kinase-mediated prostate contractions associated with impairment of β-adrenergic-cAMP-signaling pathway by chronic nitric oxide deficiency

Abstract: Impairment of nitric oxide (NO) - cyclic GMP signaling pathway is likely to contribute to human begnin prostate hyperplasia (BPH). In the present study we have used a model of chronic NO synthesis inhibition to evaluate the functional alterations of prostate smooth muscle (PSM) machinery, and involvement of Rho-kinase pathway. Wistar rats were treated with the NO inhibitor N(ω)-nitro-l-arginine methyl ester (L-NAME, 20mg/kg/day; 4 weeks), after which contractile responses to phenylephrine (α1-adrenoceptor agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In rat prostate tissues, maximum α,β- and β,γ-methylene-ATP-induced contractions amounted to approximately 80% and 100% of EFS-induced contractions (Ventura et al 2003 ). Another study reported values suggesting contractions of rat prostate tissues induced by 10 μM α,β-methylene-ATP amounting to approximately 53% of phenylephrine-induced or 64% of EFS-induced contractions (Calmasini et al 2015 ). Reported data for guinea pig prostates are again hardly conclusive, as they include average maximum contractions of 0.14 g using α,β-methylene-ATP and 0.25 g using β,γ-methylene-ATP, but only a single, representative experiment again suggesting an EFS-induced contraction of 1.1 g (Buljubasich and Ventura 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…In rat prostate tissues, maximum α,β- and β,γ-methylene-ATP-induced contractions amounted to approximately 80% and 100% of EFS-induced contractions (Ventura et al 2003 ). Another study reported values suggesting contractions of rat prostate tissues induced by 10 μM α,β-methylene-ATP amounting to approximately 53% of phenylephrine-induced or 64% of EFS-induced contractions (Calmasini et al 2015 ). Reported data for guinea pig prostates are again hardly conclusive, as they include average maximum contractions of 0.14 g using α,β-methylene-ATP and 0.25 g using β,γ-methylene-ATP, but only a single, representative experiment again suggesting an EFS-induced contraction of 1.1 g (Buljubasich and Ventura 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, no attempts have been taken to explore the sGC expression/activity in prostates from aging animals. Impairment of the β‐adrenoceptor‐cAMP signaling pathway was suggested to favor the contractile machinery in prostates from NO‐deficient rats, thus contributing to hypercontractility . A number of studies have evaluated the age‐related prostate dysfunction, but few looked at the alterations of prostate in middle‐age.…”
Section: Introductionmentioning
confidence: 99%
“…Impairment of the b-adrenoceptor-cAMP signaling pathway was suggested to favor the contractile machinery in prostates from NO-deficient rats, thus contributing to hypercontractility. 13 A number of studies have evaluated the age-related prostate dysfunction, but few looked at the alterations of prostate in middle-age. The understanding of the mechanisms that regulate the prostate reactivity in the period before the onset of old age may be important to prevent future complications and for the development of effective BPH therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The β-adrenoceptor activation counteracts the contractile pathways, contributes physiologically to maintain the prostatic tonus in several species and has been proposed as a new pharmacological therapeutic indication for BPH [37,38]. Studies in the literature have shown that impaired βadrenergic signaling plays a role in prostatic dysfunction in animal models of aging and hypertension [39,40]. However, to the best of our knowledge, no previous study evaluated this signaling pathway in prostatic tissue under obesity conditions.…”
Section: Discussionmentioning
confidence: 99%